Segmentasi Citra Luka Luar Berbasis Warna Menggunakan Teknik Active Contour - Syifa’ah Setya Mawarni; M Murinto; S Sunardi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Wounds are often underestimated by many people because sometimes all they feel is a little sore and a little bleeding. Unknowingly, wounds can cause infection which causes swelling of the skin and requires long treatment for healing. The purpose of this research is to build educational media for external wound recognition by performing image segmentation in determining wound detection using Active Contour.In the image processing process, the pre-processing stage is carried out to improve the image by removing noise. The success of image recovery was measured using MSE and PSNR values which in this study resulted in MSE = 0.1495 and PSNR = 56.43 with Uniform noise identification and a median low-pass filter of 3x3. Image processing using the Acive Contour technique can segment external wound images well using Matlab 2018b as a tool for image processing and uses 278 wound datasets with details of 59 data on burns, 85 data on abrasions, 111 data on lacerations, and 23 data on stab wounds.